Political communication in Costa Rica: the VotoCR experience - Mora Jiménez, Marlon (2014)
This work systematizes the Costa Rican experience of the recent election process and studies political communication in Costa Rica: political strategy and images towards the 2014-2018 Presidency of the Republic. It addresses the contributions in political communication inside the presidential elections campaign. It is based on the research project titled “Political communication in Costa Rica: political strategy and images towards the 2014-2018 Presidency of the Republic”, of the General Studies Center of Universidad Nacional de Costa Rica. Social media are a natural extension of the project, as well as the interactive creation of a web site, which allows communication, information, and development of systematic works in the light of the DNA of the election campaign. The investigation is presented inside the frame of the Central American Congress on Communication, “Communication as a tool for social development”.